Borazine-based inorganic–organic hybrid cyclomatrix microspheres by silicon/boron exchange precipitation polycondensation. Issue 35 (24th July 2017) - Riensch, Nicolas A.; Deniz, Ayse; Kühl, Sebastian; Müller, Lars; Adams, Alina; Pich, Andrij; Helten, Holger
Abstract : Borazine-based inorganic–organic hybrid cyclomatrix microspheres with a mean diameter of about 900 nm have been obtained via a novel silicon/boron exchange precipitation polycondensation approach. Abstract : The synthesis of borazine-based hybrid cyclomatrix polymers has been studied under various conditions. Crosslinked polymers obtained via a novel silicon/boron exchange precipitation polycondensation approach form hybrid cyclomatrix microspheres with a mean diameter of about 900 nm.